Information Quality and Digital Self-Efficacy on PLN Mobile Usage: Mediating Role of Behavioral Control - Sinung Mugiaji; Arief Budiman (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2026)
This study investigates the determinants of actual engagement within the PLN Mobile application by examining information quality and digital self-efficacy as primary antecedents. It evaluates the mediating role of perceived behavioral control in linking system attributes to actual user behavior. An explanatory quantitative design with a causal-verificative approach was applied to data from 540 active users in South and Central Kalimantan. Using purposive sampling, structural relationships were analyzed through Partial Least Squares -Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings reveal that information quality and digital self-efficacy significantly enhance both perceived behavioral control and actual usage. Perceived behavioral control acted as a significant partial mediator. The structural model explains 81.7% of the variance in behavioral control (R²= 0.817) and 94.7% in actual application usage (R²= 0.947), indicating strong explanatory power. These results confirm that psychological empowerment driven by information quality and digital confidence plays a key role in sustaining digital engagement. The sustainable utilization of digital public services in the energy sector depends largely on consumer psychological empowerment through reliable information systems and user-focused digital support. This study focuses on the Kalimantan Selatan Middle Region (Kalselteng) and uses cross-sectional data. It integrates the theory of planned behavior and the information systems success model to explain digital service adoption.